Controllable synthesis of porous iron–nitrogen–carbon nanofibers with enhanced oxygen reduction electrocatalysis in acidic medium1. Issue 62 (8th July 2015) - Yan, X. X.; Gan, L.; Fang, F.; Liu, K. X.; Luo, J.; Zhu, J.
<x xml:space="preserve">Abstract</x> Porous Fe–N–C nanofibers were synthesized as non-precious metal electrocatalysts with a 20 times enhancement in oxygen reduction performance.